اﻟﺘﻮﺟﯿﮭﺎت اﻟﺘﺮﺑﻮﯾﺔ ﻟﻠﻄﻔﻞﻓﻲ ﺳﻮرة ﻟﻘﻤﺎن (Journal of the College of Education for Women, 2019)
In the name of God the Merciful Praise be to Allah who says in his well-Aziz: (Taking Luqman said to his son, he was advising him, O sons of God Atcherk the trap of a great injustice) Luqman 13 As for after: Praise be to God, who replaced the hearts of the ruthless of female infanticide mercy and affection, and to instill in them Islamic education that have preceded the great in its field, as presented methods and techniques of effective Islamic society to this day, Vkadima were designated as simple, but today it has become Hadz scares educators and teachers in terms of numbers curriculum and the ways they deal with the child, and decisions that vary according to time and place. The Koran is for Miather in the life of the individual and society and the success of the educational process in particular and we are in a society that Islamic Arab suffering upheaval and palaces and clear as a result of globalization, which has left its impact and visible, or some communities, which had held drags the confrontation with this policy and were able to repel in the early stages and taking guard them, and educators Islamists are able to use Sciences and harnessed in its allotted according to the educational methods civilized in line with the renewal and modernization of our time, and benefit from the experience of civilized peoples for the benefit of our communities with the arms weapon sound doctrine and to avoid intrusive thoughts, and to be tempers virtuous obedience, altruism, and good sense of belonging. We will try through this study to give an idea of the most important effects of Sura Luqman and its impact on the individual and society, especially early childhood we seek to instill everything stems from the Islamic religion in accordance with educational foundations and rules of correct sound. Through this research I will address the following topics: 1- Islamic Education and images from the Holy Quran 2- Quranic stories and role in Islamic education 3 - Sura Luqman between Islamic education and the correct setting and inspired by the lessons of.